Three billboards outside Ebbing, Missouri - McDonagh, Martin (Faber & Faber, 2017)
"After months pass without a culprit in her daughter's murder, Mildred Hayes pays for three signs challenging the authority of William Willoughby, the town's revered chief of police. When his second-in-command, Officer Dixon, a mother's boy with a penchant for violence, gets involved, the battle between Mildred and Ebbing's law enforcement threatens to engulf the town." Page 4 of cover.